2004
DOI: 10.1002/asi.20127
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a model of information seeking over multiple search sessions

Abstract: Most information systems share a common assumption: information seeking is discrete. Such an assumption neither reflects real-life information seeking processes nor conforms to the perspective of phenomenology, "life is a journey constituted by continuous acquisition of knowledge." Thus, this study develops and validates a theoretical model that explains successive search experience for essentially the same information problem. The proposed model is called Multiple Information Seeking Episodes (MISE), which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 27 publications
1
68
0
Order By: Relevance
“…For example, Spink, Ozmutlu, and Ozmutlu (2002) found that the length of search queries and the time costs in multitasking sessions are longer than those in mono-tasking sessions. Lin and Belkin (2005) also confirmed that the average number of search queries used in multitasking sessions is more than that in mono-tasking sessions. When Lucchese et al (2011) analyzed the search logs of 307 search sessions and 1,424 queries from American On Line (AOL), they found that the average duration of each search session was about 15 minutes.…”
Section: Multi-tasking Web Searchsupporting
confidence: 69%
“…For example, Spink, Ozmutlu, and Ozmutlu (2002) found that the length of search queries and the time costs in multitasking sessions are longer than those in mono-tasking sessions. Lin and Belkin (2005) also confirmed that the average number of search queries used in multitasking sessions is more than that in mono-tasking sessions. When Lucchese et al (2011) analyzed the search logs of 307 search sessions and 1,424 queries from American On Line (AOL), they found that the average duration of each search session was about 15 minutes.…”
Section: Multi-tasking Web Searchsupporting
confidence: 69%
“…It is in line with multisession studies (Lin & Belkin, 2005;Vakkari & Hakala, 2000) and some integrated behavioral studies Vakkari et al, 2003;Xie, 2000) that open the black box of each stage and look into the interaction among activity elements driving the development of the process.…”
Section: Interactive Information Retrieval Activitymentioning
confidence: 97%
“…Information-seeking behavior could last for a long period with multiple search sessions or for just one session (Belkin & Vickery, 1985;Lin & Belkin, 2005). Here a search session is defined as the continuous interaction between a user and an information system without major interruption of activities for purposes irrelevant to the information-seeking task.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A repeated search can, therefore, be a request for the same information, for new information, or for different information-even though the search requests may appear very similar. Lin and Belkin (Lin, 2005;Lin & Belkin, 2005) demonstrate elegantly how complex is the nature of successive searching compared to the idealized one-iteration model.…”
Section: Themesmentioning
confidence: 99%